PENGARUH PRAKTIK SPIRITUALITAS DALAM KEHIDUPAN KERJA TERHADAP KINERJA ANGGOTA KEPOLISIAN DI POLDA NTB - Toni Prabowo (Yayasan Nusantara Hasana Berdikari, 2024)
This study aims to analyze the influence of spiritual practices in the workplace on the performance of police officers at the Nusa Tenggara Barat (NTB) Regional Police. The research method employed is a quantitative approach with a simple regression research design. The study population consists of police officers working at NTB Regional Police, with a randomly selected sample of 100 respondents. Data were collected through questionnaires measuring the level of spiritual practices and the performance of police officers. The analysis results indicate that spiritual practices have a positive and significant influence on police officer performance, with a regression coefficient showing a strong relationship between these two variables. These findings are consistent with previous studies suggesting that workplace spirituality can enhance individual performance. This study concludes that integrating spiritual values in the work environment can contribute to improving police officer performance, and it is recommended that NTB Regional Police management implement spiritual practices in human resource development policies to achieve optimal performance.